The Effect of Fundamental Taekwondo Training on the Fundamental Movement Skills of Elementary School Students - Salma Fadilah; Dian Budiana; Ricky Wibowo (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of fundamental Taekwondo training on fundamental movement skills (FMS) in elementary school students. The research method used a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 25 students (10 boys and 15 girls) from the Lembang Taekwondo Club. The instrument used was the Test of Gross Motor Development–Second Edition (TGMD-2) to measure children’s locomotor movement abilities. Data analysis using the Shapiro-Wilk normality test showed that the data were normally distributed (p > 0.05), while the paired sample t-test yielded a significance value of 0.000 < 0.05. There is a clear improvement from the pretest results, where most students were in the average (60%) and below average (32%) categories.After being given treatment in the form of fundamental taekwondo training, the posttest results show that the excellent category increased to 32%, above average to 28%, and average remained at 32%. while the below average category decreased to 8%. This indicates a significant difference between the pretest and posttest results. This finding suggest that the training program was well received and successfully implemented by the childern. Thus, fundamental Taekwondo training has a positive effect on improving the fundamental movement skills of elementary school students, particularly in terms of balance, coordination, and movement strength.